Balkan endemic nephropathy: an update on its aetiology - Stiborová, Marie; Arlt, Volker M; Schmeiser, Heinz H (Archives of toxicology, 2016)
Balkan endemic nephropathy (BEN) is a unique, chronic renal disease frequently associated with upper urothelial cancer (UUC). It only affects residents of specific farming villages located along tributaries of the Danube River in Bosnia-Herzegovina, Croatia, Macedonia, Serbia, Bulgaria, and Romania where it is estimated that ~100,000 individuals are at risk of BEN, while ~25,000 have the disease. This review summarises current findings on the aetiology of BEN. Over the last 50 years, several hypotheses on the cause of BEN have been formulated, including mycotoxins, heavy metals, viruses, and trace-element insufficiencies. However, recent molecular epidemiological studies provide a strong case that chronic dietary exposure to aristolochic acid (AA) a principal component of Aristolochia clematitis which grows as a weed in the wheat fields of the endemic regions is the cause of BEN and associated UUC. One of the still enigmatic features of BEN that need to be resolved is why the prevalence of BEN is only 3-7 %. This suggests that individual genetic susceptibilities to AA exist in humans. In fact dietary ingestion of AA along with individual genetic susceptibility provides a scenario that plausibly can explain all the peculiarities of BEN such as geographical distribution and high risk of urothelial cancer. For the countries harbouring BEN implementing public health measures to avoid AA exposure is of the utmost importance because this seems to be the best way to eradicate this once mysterious disease to which the residents of BEN villages have been completely and utterly at mercy for so long.
Keywords: semena rostlinná; Europe, Eastern; Triticum; Drug Resistance; Carcinogens, Environmental; Confounding Factors, Epidemiologic; faktory vyvracející (epidemiologie); Crops, Agricultural; Plant Weeds; Flour; balkánská nefropatie; zemědělské plodiny; prevalence; Aristolochia; Kidney; pšenice; Urologic Neoplasms; Environmental and genetic factors; medicína založená na důkazech; plevel; Endemic Diseases; karcinogeny životního prostředí; léková rezistence; Aristolochic Acids; Seeds; Aristolochic acid nephropathy; dieta; mouka; Disease aetiology; kyseliny aristolochové; kontaminace potravin; Animals; lidé; Balkan Nephropathy; Aristolochic acid; Food Contamination; ledviny; zvířata; Humans; Prevalence; Diet; východní Evropa; Risk; Balkan endemic nephropathy; Evidence-Based Medicine; Upper urothelial cancer; urologické nádory; riziko; endemické nemoci